Sum-rate maximisation for two-way AF MIMO relaying networks and random antenna selection. (2016) - Sayeb, Rahima; Hamdi, Noureddine
This paper considers a multiple-input multiple-output (MIMO) two-way relaying network, where two-source nodes exchange data via a half-duplex amplify-and-forward (AF) relay. In this paper, we propose an efficient random antenna selection strategy based on maximising the sum-rate and minimising the power consumption. The proposed strategy involves choosing the best transmit and receive antennas at the two sources based on the maximisation of the overall sum-rate. The key design criterion is to reduce transmit radio frequency chains in order to minimise the energy consumption of the system. In the first step, transmit and receive antennas will be selected randomly. In the second step, signal-to-noise ratios (SNRs) of randomly chosen antennas are compared with a predefined threshold γ th . If the SNRs of the selected antennas are higher than the predefined threshold, these antennas will be chosen for the communication. Else another random selection is used. Also, we show that for the problem of sum-rate maximisation related to the introduced system, the optimal relay matrix have a general beamforming structure. Simulations demonstrate the performance of the proposed algorithm.